1986
DOI: 10.1159/000249319
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Brittle Nails

Abstract: Only few reports exist about the occurrence of brittle nails. We examined 1,584 persons with respect to the incidence of this anomaly. The patients were from five different groups: outpatients of a dental clinic, blood donors, residents of an old people’s home, patients of a clinic for internal diseases and patients of a general practice. Approximately 20% of the subjects examined had brittle nails. Women suffered from brittleness of nails much more frequently than men (27 vs. 13%) with a ratio of men to women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
0
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 0 publications
1
25
0
3
Order By: Relevance
“…The incidence rate of brittle nails in other European countries and in North America is thought to be similar [2], The term brittle nails includes lamellar dystro phy (onychoschizia) as well as roughness and splitting of the free edge of the nail [3]. In an earlier study, we found a much higher incidence of brittle nails in women aged between 15 and 50 years as compared to men [1]. The fact that brittle nails are much more common in females could be either due to a constitutional characteristic or otherwise indicate sex-specific environmental factors.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…The incidence rate of brittle nails in other European countries and in North America is thought to be similar [2], The term brittle nails includes lamellar dystro phy (onychoschizia) as well as roughness and splitting of the free edge of the nail [3]. In an earlier study, we found a much higher incidence of brittle nails in women aged between 15 and 50 years as compared to men [1]. The fact that brittle nails are much more common in females could be either due to a constitutional characteristic or otherwise indicate sex-specific environmental factors.…”
mentioning
confidence: 73%
“…About 20% of the German population show symptoms of brittle nails [1]. The incidence rate of brittle nails in other European countries and in North America is thought to be similar [2], The term brittle nails includes lamellar dystro phy (onychoschizia) as well as roughness and splitting of the free edge of the nail [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
Originalien Hintergrund und FragestellungBrüchige, splitternde wie auch weiche Nä-gel sind ein sehr häufiges Problem, unter dem ungefähr 20% der Bevölkerung leiden, wobei Frauen etwa doppelt so häufig betroffen sind wie Männer [12,17,21,22]. Klinisch können -isoliert oder kombiniert -vermehrte Brüchigkeit der Nagelplatte mit schichtweisem Abblättern vom distalen Rand (Onychoschisis) und/oder längsfaserigem Aufsplittern (Onychorrhexis) sowie bröckliges oder querlaufendes Abbrechen beobachtet werden, wobei der Begriff "brüchige Nägel" klinisch wie auch pathogenetisch nicht eindeutig definiert ist [12,22].
…”
unclassified
“…Klinisch können -isoliert oder kombiniert -vermehrte Brüchigkeit der Nagelplatte mit schichtweisem Abblättern vom distalen Rand (Onychoschisis) und/oder längsfaserigem Aufsplittern (Onychorrhexis) sowie bröckliges oder querlaufendes Abbrechen beobachtet werden, wobei der Begriff "brüchige Nägel" klinisch wie auch pathogenetisch nicht eindeutig definiert ist [12,22]. Abgesehen von den medizinisch relevanten Onychodystrophien bei Pilzerkrankungen oder spezifischen Dermatosen wie Psoriasis und Lichen ruber und dem behandlungsbedürftigen "brittle nail syndrom" (BNS), wird für brüchige Nägel kosmetisch relevanter Ausprägung v. a. eine durch extrinsische Einflüsse bedingte Auflösung der Zementsubstanz zwischen den Hornlamellen der Nagelplatte mit nachfolgender Dehydratation verantwortlich gemacht [13,17,22].…”
unclassified